2008
DOI: 10.1007/s11249-008-9348-8
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction by Dimples on Surfaces in Plane–Plane Contact Lubrication

Abstract: An experimental system was designed to evaluate the drag reduction by dimples on surfaces in plane-plane contact lubrication. Because of the dimples on the surfaces, in some of the experiments, it was observed that stable gas bubbles existed in the lubricant film. The results of the experiments showed that the existence of gas was decided by the depth of dimples and the volume of lubricant supply; the deeper the dimples were and the less the lubricant supply, the higher the probability of gas existence. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Therefore, it is difficult to develop a model and a theoretical result on the real experiment, so here only an approximate theoretical analysis was employed to discuss the trend of the experimental result. The effects of dimple depth on lubrication and the existence of gas were discussed based on Reynolds equation in Wang, et al (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is difficult to develop a model and a theoretical result on the real experiment, so here only an approximate theoretical analysis was employed to discuss the trend of the experimental result. The effects of dimple depth on lubrication and the existence of gas were discussed based on Reynolds equation in Wang, et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the bubbles are large enough to exist entirely between a pair of surfaces over some of the contact area, the effect of these bubbles on the lubrication is different from the entrained bubbles (Wang,et al (23)). In the Wang, et al (23), it was pointed out that the pressure in the bubbles induced by the surface tension can balance load and also reduce friction if enough gas exists between a pair of surfaces. Only the effect of dimple depth was discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Their result showed that the adhesion decreases because of the dimple effect and the drill's lifetime is lengthened, when these dimples were distributed in an overlapped triangular way. Wang et al obtained the optimal ratio of a rectangular dimple's depth to the clearance between parallel textured surfaces, with which the best lubrication performance for tribological pairs can be obtained [13]. Kango distributed rectangular dimples can be reduced compared with that of the untextured bearing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 8 designed an experimental system to evaluate the drag reduction by dimples in a lubricated plane-plane contact. They observed stable gas bubbles, indicating existence of cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Ryk et al 7 reported that friction could be reduced by up to 40% using evenly distributed, hemispherical micro-pockets over the whole stationary surface of a parallel bearing under reciprocating sliding motion. Wang et al 8 designed an experimental system to evaluate the drag reduction by dimples in a lubricated plane–plane contact. They observed stable gas bubbles, indicating existence of cavitation.…”
Section: Introductionmentioning
confidence: 99%